Diversity of culicids and molecular analysis of arboviruses in Aedes spp. larvae from Costa Rica (UNED Research Journal, 2025)
Introduction: Understanding mosquito diversity, monitoring new species, and recognizing the role of vertical transmission are crucial to effective vector-borne disease management. Objective: To estimate culicid diversity and detect dengue, chikungunya, and Zika viruses in Aedes spp. larvae across 19 districts in Costa Rica. Methods: From August through November 2021, we collected 5 036 mosquito larvae in 26 localities, identified them taxonomically, analyzed them for diversity indices, and used real-time Polymerase Chain Reaction to detect viral RNA in Aedes spp. larvae. Results: We identified eight species of Culicidae, with Aedes aegypti being the most abundant (63.3%), followed by Aedes albopictus (13.9%), which is reported for the first time for Punta Morales. None of the 97 larval pools tested positive for dengue, chikungunya, or Zika. Conclusion: The larval composition exhibited low ecological diversity and no viral infection, indicating limited vertical transmission during the study period, while underscoring the need for sustained entomological surveillance.
Keywords: mosquitoes; arthropods; dengue; chikungunya; Zika; biodiversity; distribution